REMEMBERING: HALF A CENTURY OF PHYSICAL EDUCATION IN EUROPE (Fiep Bulletin - online, 2012)
The paper presents a quick overview of the evolution of the idea of physical education in Europe inthe last 50 years and provides a view of the tendencies of the 20th century, among which are thepedagogical, the psychomotor and the sporting trends. This overview aims at showing the difficulties andconstraints in the task of those who are in charge of teaching the educators. The discussion, based uponthe traditional division of the philosophical thought (metaphysics, logic, axiology and epistemology), isstructured considering both ends of the dialectic field: objectivity and subjectivity or culture and nature.According to the paper, the way to better approach the secular conflict of nature in opposition to culturelies in comparing the advantages and disadvantages of each view presented.
Keywords: physical education; philosophical thought; culture; nature; tendencies.